2018
DOI: 10.1557/mrc.2018.138
|View full text |Cite
|
Sign up to set email alerts
|

In situ electrochemical polymerization of poly(3,4-ethylenedioxythiophene) (PEDOT) for peripheral nerve interfaces

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The authors showed that 50% of the cells exposed to EDOT (0.1 m ) remained viable after 72 h and that the neurons were still intact 3 h after the electropolymerization. This strategy proved applicable to the in situ injection of electrodes within individual peripheral nerves …”
Section: Physical Approachesmentioning
confidence: 99%
“…The authors showed that 50% of the cells exposed to EDOT (0.1 m ) remained viable after 72 h and that the neurons were still intact 3 h after the electropolymerization. This strategy proved applicable to the in situ injection of electrodes within individual peripheral nerves …”
Section: Physical Approachesmentioning
confidence: 99%
“…[191] Murbach et al electropolymerized EDOT in peripheral nerves directly to generate a soft, injectable conductive polymer electrode that is capable of bi-directional communication. [192] Innovations in enhancing and diversifying the mechanical and electrical properties of conducting polymer materials will foster the development of novel wearable and implantable sensor devices for neuroelectronic applications.…”
Section: Recent Materials Innovations: Development Of Pedot-based Stretchable Devices and Complementary Circuitsmentioning
confidence: 99%
“…Living cells and tissues exhibit and respond to electrical potentials in the form of naturally occurring bioelectricity, important for tissue development and regeneration, or exogenously delivered electric current via, for example, electrodes as medical devices . Cellular responses include galvanotaxis, increased intracellular calcium concentration, extracellular matrix assembly, and associated cell proliferation and differentiation .…”
mentioning
confidence: 99%